Understanding Digital Literacy Using Film: Case Study of Netflix’s The Social Dilemma - Putri, Aliva Pudyas Permata; Hersinta (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Social media may have been glorified as something helpful, easy and convenient but as we all know it must have two sides of a coin. Social media does have quite a lot of bad sides. Unfortunately, the majority of mass media only share the good and glorify it, without telling the dark side of it that is even more complex than it explained. This study uses a qualitative approach with Stuart Hall’s reception analysis theory to understand the audience's role in generating meaning of digital literacy. The literature review highlights the previous research on the spread of misinformation and the solutions proposed by tech giants and experts, which aligns with the current research on digital literacy for social media. Through this research participants show that they understand digital literacy better after watching “The Social Dilemma” documentary film. Digital literacy is a very important skill that people must understand. This film proves that digital literacy can be taught and understood by watching this film